(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Retinopathy is a major T2DM complication that still to be a worldwide cause of curable and avoidable vision loss. Materials and Methods: The current study protocol included study the impact of BMI on some glycemic control markers (fasting blood glucose (FBG), glycated hemoglobin (HbA1C), insulin, insulin sensitivity (IS)and insulin resistance (IR)) and some oxidative stress markers (reactive oxygen species (ROS), total antioxidant, capacity (TAC), and oxidative stress index (OSI). Also, the present study included an important epigenetic parameter: the global DNA methylation. Results: Patients were divided into four BMI categories: (normal, overweight, obesity and over obesity), the highest percent for both patients were within obesity group. The highest levels of FBG were in obesity and morbid obesity in both retinopathy and T2DM. Highest levels of HbA1C in Morbid obesity were compared with other BMI groups in T2DM only. Insulin and IR showed a significant raise in obesity and morbid obesity in retinopathy and T2DM. IS significantly decreased in morbid obesity compared with others. Methylation analysis revealed that patients with diabetes (T2DM and retinopathy) had a significantly increase in levels of 5mC% compared healthy subjects. Also, a significant increase was recorded in retinopathy compared with T2DM. In all of the studied groups, the correlation analysis found a significant positive association between BMI and 5mC %. Conclusion: The positive correlation between BMI and DNA methylation can lead to adverse effects for diabetes patients, which may lead to the progression of retinopathy.